2019
DOI: 10.1039/c8tb03359e
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and regulation of the corrosion resistance of macroporous titanium scaffolds with bioactive surface films for biomedical applications

Abstract: A three-layer bioactive film on porous titanium was constructed and evaluated for its corrosion resistance via electrochemical analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…The fast oxidation meant that the samples were oxidized at 10 mA until the voltage climbed to 30 V, and the slow oxidation indicated that the samples were in turn oxidized at 1 mA for 30 min, 5 mA for 30 min and 10 mA until the voltage reached 30 V. Figure 2c shows the surface microstructure of the AHAO-treated samples. The D-TiO 2 layer formed between the pTi substrate and the surface L-TiO 2 layer resulted from AH treatment, as was in line with our previous report [ 30 ]. Under fast oxidation, some microcracks occurred on the surface, and the observation on the cross-section morphology showed that the L-TiO 2 layer had the tendency to fall off.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The fast oxidation meant that the samples were oxidized at 10 mA until the voltage climbed to 30 V, and the slow oxidation indicated that the samples were in turn oxidized at 1 mA for 30 min, 5 mA for 30 min and 10 mA until the voltage reached 30 V. Figure 2c shows the surface microstructure of the AHAO-treated samples. The D-TiO 2 layer formed between the pTi substrate and the surface L-TiO 2 layer resulted from AH treatment, as was in line with our previous report [ 30 ]. Under fast oxidation, some microcracks occurred on the surface, and the observation on the cross-section morphology showed that the L-TiO 2 layer had the tendency to fall off.…”
Section: Resultssupporting
confidence: 91%
“…Besides, the AH or other surface-modified pTi was reported to have osteoinductivity when ectopically implanted into the body of the experimental animal for 5 months or longer time [ 14 , 38 , 39 ]. With additional AO treatment, both AHAO and AHAOEDHT samples exhibited the increased corrosion resistance in our previous study [ 30 ]. However, the AHAO sample showed weaker apatite-forming ability than the AHAOEDHT one.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations